2021
DOI: 10.1111/birt.12554
|View full text |Cite
|
Sign up to set email alerts
|

Mental health among pregnant women with COVID‐19–related stressors and worries in the United States

Abstract: Background Few studies have evaluated whether pandemic‐related stressors, worries, and social distancing have affected the mental health of pregnant women during the COVID‐19 pandemic. Methods Data came from an online survey of United States pregnant women (n = 715), conducted in May 2020. The Edinburgh Postnatal Depression Scale and Generalized Anxiety Disorder Scale were used to assess depressive symptoms, thoughts of self‐harm, and moderate or severe anxiety. Multipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
48
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 32 publications
3
48
0
1
Order By: Relevance
“…These findings elevate concerns about the impact of COVID-19-related stressors on mental health outcomes in pregnant and postpartum women, particularly given the chronic and widespread nature of these experiences. Indeed, since the start of the COVID-19 pandemic, studies across the globe have observed high rates of depression and anxiety in perinatal women 15 18 . Preventing or attenuating perinatal mood and anxiety disorders is essential for preventing a sequelae of intergenerational transmission and negative developmental consequences.…”
Section: Introductionmentioning
confidence: 99%
“…These findings elevate concerns about the impact of COVID-19-related stressors on mental health outcomes in pregnant and postpartum women, particularly given the chronic and widespread nature of these experiences. Indeed, since the start of the COVID-19 pandemic, studies across the globe have observed high rates of depression and anxiety in perinatal women 15 18 . Preventing or attenuating perinatal mood and anxiety disorders is essential for preventing a sequelae of intergenerational transmission and negative developmental consequences.…”
Section: Introductionmentioning
confidence: 99%
“…Reduced inperson antenatal visits may have contributed to these findings. 40,41 Also, high levels of prenatal stress and anxiety, which have been reported in pregnant women exposed to the pandemic-related lockdown 35,[60][61][62][63][64][65][66][67][68][69][70][71] and are risk factors for PTB, 72,73 might have played a role. Another possible explanation includes change in the referral patterns with more high-risk women referred to our university center.…”
Section: Discussionmentioning
confidence: 99%
“…d Assessed at hospital discharge. mother and her fetus and the radical changes swiftly implemented in labor and birth care 35,[60][61][62][63][64][65][66][67][68][69][70][71] might explain this increase and its temporal trend.…”
Section: Discussionmentioning
confidence: 99%
“…35 Pandemic related stressors, worries and social distancing have affected the mental health of pregnant women, with a high percentage of them having symptoms of depression and anxiety. 36 Therefore role played by a birth companion under these circumstances is of a higher magnitude than ever before.…”
Section: Introductionmentioning
confidence: 95%